Does brand personality and perceived product quality play a major role in mobile phone's consumers switching behaviour? - Nikhashemi, Seyedrajab *; Valaei, Naser *; Tarofder, Arun Kumar (Sage, 2017)
This study’s main objective is to explore the antecedents of consumer switching behaviour in the mobile industry’s context. At the same time, this study gives a closer focus on the roles that brand personality (BP) and perceived product quality play in customer satisfaction, consumer brand identification, and switching behaviour. Using a self-structured questionnaire, 381 usable responses were recorded for data analysis. Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis, and Structural Equation Modelling were employed to analyse the data. The EFA outcome reveals that excitement, competence, and sophistication are the most significant qualities predicting BP in the mobile industry’s context. The result demonstrates that BP, indirectly through consumer brand identification and customer satisfaction, has a negative effect on consumer’s switching behaviour intention. Perceived product quality has a direct and indirect relationship with switching behaviour intention. Finally, it is revealed that BP has high impact on perceived product quality’s evaluation as well.